2017
DOI: 10.3892/or.2017.6120
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‑27a promotes the proliferation and inhibits apoptosis of human pancreatic cancer cells by Wnt/β-catenin pathway

Abstract: A specific expression of miRNA in pancreatic cancer renders it the novel diagnostic marker of pancreatic cancer. Therefore, we investigated how the anticancer effect of miRNA‑27a suppressed cell growth and induced apoptosis of human pancreatic cancer cells. We upregulated miRNA‑27a expression in PANC-1 cells using miRNA‑27a mimic, which demonstrated that induction of cell growth and suppression of apoptosis of human pancreatic cancer cells were observed. However, anti‑miRNA‑27a inhibited cell growth and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…It is well known that miRNA is essential for regulating gene expression, 7 and studies have shown that miRNA can serve as an active role in the promotion or suppression of numerous cancers 8 . Simultaneously, miRNA has also been reported to be involved in controlling biological processes, including cell growth, apoptosis, 9 and cell cycle 10 . For instance, miR‐137 was downregulated in OSCC and related to tumor differentiation, 11 and upregulation of miR‐101 significantly suppressed the proliferation, apoptosis resistance, migration, and invasion of OSCC cells 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that miRNA is essential for regulating gene expression, 7 and studies have shown that miRNA can serve as an active role in the promotion or suppression of numerous cancers 8 . Simultaneously, miRNA has also been reported to be involved in controlling biological processes, including cell growth, apoptosis, 9 and cell cycle 10 . For instance, miR‐137 was downregulated in OSCC and related to tumor differentiation, 11 and upregulation of miR‐101 significantly suppressed the proliferation, apoptosis resistance, migration, and invasion of OSCC cells 12 .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a species of the non-protein coding RNA family, represented by short, single-stranded RNA approximately 18–22 nucleotides in length, and are the key regulators of post-transcriptional gene expression [8, 9]. Importantly, studies suggested a high association between abnormal miRNA expressions and the development and progression of numerous cancer types [9–12].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, a study was performed on the miRNA27a and its association with pancreatitis cancer (27). In this study, While miRNA27a mimic was applied to overexpress the miRNA27a, an anti miR27a was applied to lower express the same (27). The results demonstrated that the overexpression of hsa-miR-27a-3p leads to cell growth and apoptosis prevention, while the lower expression of it leads to cell growth prevention, leading the cell to apoptosis (27).…”
Section: Discussionmentioning
confidence: 95%
“…In 2018, a study was performed on the miRNA27a and its association with pancreatitis cancer (27). In this study, While miRNA27a mimic was applied to overexpress the miRNA27a, an anti miR27a was applied to lower express the same (27).…”
Section: Discussionmentioning
confidence: 99%